Mortalidad relacionada a niveles de lactato en pacientes adultos con sepsis y choque séptico que ingresan al servicio de urgencias, en el Hospital General Regional No. 1 del IMSS - Baldivias Lunar, Luis Fernando (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Sepsis, defined as a dysregulated, life-threatening host response to an infectious agent, is one of the diseases with the highest rates of morbidity and mortality. Septic Shock requires the presence of Sepsis associated with clinical and biochemical parameters. Lactate or lactic acid is a chemical compound as a result of glucose metabolism produced by body tissues under conditions of hypoperfusion that reflects cellular dysfunction in patients with sepsis and septic shock. Elevated lactate levels indicate hypoperfusion imbalance and are associated with increased mortality in patients with sepsis and septic shock. Objective: To determine the relationship between blood lactate levels and mortality in patients diagnosed with sepsis and septic shock admitted to the emergency room at HGR No. 1 IMSS Charo, Michoacán, from January to September 2021. Material and method: Retrospective, observational, cross-sectional and descriptive study in patients diagnosed with sepsis and septic shock who attended the 2021 emergency area of HGR No 1 from January to September. Results: 109 patients were registered, of which 72 patients correspond to diagnosis from sepsis and 37 to septic shock; A total of 31 patients died, 12 with an initial diagnosis of sepsis and 19 due to septic shock; demonstrating a direct relationship between lactate levels >2 mmol/lt and high mortality with 90% of deaths in patients with septic shock and hyperlactatemia. Conclusions: Lactate levels >2 mmol/lt on admission to the emergency department in patients with sepsis and septic shock, is directly associated with higher mortality independent of sociodemographic factors.

Sepsis, definida como una respuesta desregulada del huésped, potencialmente mortal ante un agente infeccioso es una de las enfermedades con más altos índices de morbilidad y mortalidad. El Choque Séptico requiere de la presencia de Sepsis asociada a parámetros clínicos y bioquímicos. El lactato o ácido láctico, es un compuesto químico como resultado del metabolismo de la glucosa producido por los tejidos corporales en condiciones de hipoperfusión que refleja la disfunción celular en pacientes con sepsis y choque séptico. Niveles elevados de lactato indican un desequilibrio por hipoperfusión y se asocian a una mayor mortalidad en pacientes con sepsis y choque séptico. Objetivo: Determinar la relación entre los niveles de lactato en sangre con la mortalidad en pacientes con diagnóstico de sepsis y choque séptico que ingresan al área de urgencias en el HGR No. 1 IMSS, Charo, Michoacán, de enero a septiembre del 2021. Material y método: Estudio retrospectivo, observacional, transversal y descriptivo en pacientes con diagnóstico de sepsis y choque séptico que acudieron de enero a septiembre al área de urgencias 2021 de HGR No 1. Resultados: Se registraron 109 pacientes de los cuales 72 pacientes corresponden a diagnóstico de sepsis y 37 a choque séptico; fallecieron un total de 31 pacientes, 12 con diagnóstico inicial de sepsis y 19 por choque séptico; demostrando relación directa entre niveles de lactato >2 mmol/lt y mortalidad elevada con un 90% de muertes en pacientes con choque séptico e hiperlactatemia. Conclusiones: Niveles de lactato >2 mmol/lt al ingreso al servicio de urgencias en pacientes con sepsis y choque séptico, se asocia de manera directa a mayor mortalidad independiente a factores sociodemográficos.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Urgencias Médicas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16389; info:eu-repo/classification/cti/3; FCMB-E-2023-0581; Choque séptico; Lactato; Mortalidad